Tissue printing technique in nitrocelullose membranes: a rapid detection technique for estimating incidence of pvx, pvy, pvs and plrv viruses infecting potato (solanum spp.) (2002)
The ELISA serological technique has been used since the 1970s as a quantative technique for the detection of many groups of virus which infect plants. The immune-impression (IMI) in nitrocelullose membrane qualitative technique has been implemented more recently for the detection of different viral groups. In this work, the IMI technique has been adapted for the detection of PVX, PVY PVS and PLRV viruses which attack different species and varieties of potato crop (Solanum spp.), such as Egg yolk, Capiro, Morita, Pastusa, Monserrate, Tuquerreña, ICA Puracé and ICA Nariño, all from the Nariño department. The four viruses mentioned above can cause 30% and 60% losses in production, be they acting alone or synergistically. This means that they can easily reduce the economic benefits of a country like Colombia, characterised as being a great potato producer (i.e. more than 2.8 million tons per year). The IMI technique was compared with the ELISA technique (Enzymne Linked Immunosorbent Assay) using the same samples, leading to confirmation of the test's sensitivity for detecting the virus. From a total of 800 samples analyzed by IMI from different areas in the Nariño department, 72% incidence for PVY, 38.7% for PVX, 85.6% for PVS and 91.1% for PLRV was found; these estimates were similar or greater than those obtained using ELISA. These results are new for Colombia in terms of imple-menting the easy and sensitive IMI technique for detecting these four viral groups infecting the potato as well as estimating their incidence in Nariño, one of Colombia's most important potato-producing departments. The opportune and flexible detection of virus leads to an effective response to eradicating contaminated material, both material in the field as well as that from in vitro culture. Results lead to it being suggested that implementing IMI could bringing wide benefits for potato seed certification programmes, as they maintain sensitivity and specificity, they reduce costs and can be participative.